2001
DOI: 10.1007/s15010-001-1065-2
|View full text |Cite
|
Sign up to set email alerts
|

Meningitis in a Girl with Recurrent Otitis Media Caused by Streptococcus pyogenes - Otitis Media Has to Be Treated Appropriately

Abstract: Streptococcus pyogenes rarely causes meningitis. A recent increase in the incidence and severity of diseases due to S. pyogenes has been observed worldwide, without an apparent increase in the incidence of S. pyogenes meningitis. However, more recently severe and fulminant cases of S. pyogenes meningitis have been reported in the literature. This case report emphasizes the fact that S. pyogenes can cause meningitis with severe clinical sequelae such as hygromas and right-sided third cranial nerve palsy. Most i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 12 publications
0
7
0
5
Order By: Relevance
“…Generally, it is not present as a complication of the invasive disease and there is frequently an association with contiguous infectious foci of the upper respiratory tract. Furthermore, some risk factors have been described: neurosurgery, skull fractures, CSF leaks, infection or colonization of the upper respiratory tract and skin lesions (impetigo, varicella and erysipelas) [1,5]. However, SPM also occurs in healthy individuals that do not have predisposing conditions and do not present clear evidences of a contiguous focus [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, it is not present as a complication of the invasive disease and there is frequently an association with contiguous infectious foci of the upper respiratory tract. Furthermore, some risk factors have been described: neurosurgery, skull fractures, CSF leaks, infection or colonization of the upper respiratory tract and skin lesions (impetigo, varicella and erysipelas) [1,5]. However, SPM also occurs in healthy individuals that do not have predisposing conditions and do not present clear evidences of a contiguous focus [3].…”
Section: Discussionmentioning
confidence: 99%
“…In SPM during infancy, the evolution to neurological complications and sequelae are described in 60% of the cases, with a mortality rate of up to 12% [1,3]. Chow & Muder reported a global lethality of 5% and sequelae in 46% of the cases in a review conducted between 1981 and 1991 [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent reviews of the literature 2,3 that addressed confirmed cases of GAS meningitis among children and adults in the past 3 decades found only 2 children with brain abscesses, 2 children with subdural hygromas (1 of whom required surgical drainage and shunt insertion), 13 and none with a subdural empyema. Subsequent cases of pediatric GAS meningitis with a subdural hygroma 14 and an empyema 15 have been reported. However, none of these children experienced varicella before the episode of GAS meningitis.…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Steppberger et al 9 , as meningites causadas por S. pyogenes são bastante raras e quando ocorrem, costumam ter um prognóstico ruim, com elevada taxa de óbito ou seqüelas importantes.…”
Section: Introductionunclassified